Best Practices in Customs Procedures - Ioan Popa; Mihaela Gabriela Belu; Dorel Mihai Paraschiv; Ana Maria Marinoiu (Amfiteatru Economic Journal, 2015)
The paper presents the main aspects related to the modernisation process of the European Union customs legislation and identifies a series of benefits that arise from implementing the measures of the Modernised Community customs code. In this context, foreign trade companies must adapt their logistics strategies to the new customs system, a necessary condition in order to obtain competitive advantages. In an increasingly competitive global environment, best practices in the customs activity have a positive influence both on the international trade as well as on the consumer safety and protection. The results of implementing best practices are also found in rankings made by different institutions and international organisations regarding the competitiveness in logistics and ease in the development of foreign trade transactions. They mainly relate to reducing the time for the necessary clearance procedure and reducing the logistics costs by decreasing the number of physical and documentation checks, giving a priority treatment to consignments when they are selected for control, the possibility to choose the location for customs controls and less information to submit in summary declarations.
Keywords: F23; K33; K39; 330; best practices; customs; customs procedures; international trade; logistics performance index